Specific variants in ftsI reduce carbapenem susceptibility in Pseudomonas aeruginosa - Hirokazu Yano; Noboru Nakata; Koji Yahara; Motoyuki Sugai; Yukari Sato (Microbiology Spectrum)
ABSTRACT The ftsI locus of gram-negative bacteria encodes penicillin-binding protein 3 (PBP3), a common target of β-lactam antibiotics. Recent genomic surveillance of carbapenem-resistant Pseudomonas aeruginosa revealed that 17% of strains possessed nonsynonymous substitution in ftsI. However, the contribution of ftsI nonsynonymous substitution alone to the antimicrobial susceptibility of P. aeruginosa has not been formally evaluated. Therefore, we assessed the effect of ftsI nonsynonymous substitutions alone on β-lactam susceptibility in recombinant P. aeruginosa strains. The nonsynonymous substitutions C265G (Leu89Val), C1379T (Met460Thr), T1412G (Val471Gly), C1510T (Arg504Cys), C1579A (Pro527Thr), C1579T (Pro527Ser), C1599A (Phe533Leu), and G1609C (Val537Leu) were introduced into ftsI in an antimicrobial-susceptible strain via homologous recombination. Then, their β-lactam susceptibilities were investigated using the broth microdilution method and growth parameter analysis for the growth curves. The introduction of the N-terminal Leu89Val mutation did not alter β-lactam susceptibility. By contrast, the introduction of penicillin-binding (PB) domain mutations (Met460Thr, Val471Gly, Arg504Cys, Pro527Thr, Pro527Ser, Phe533Leu, or Val537Leu) reduced the susceptibility to meropenem and doripenem by two- to eightfold in MIC. Arg504Cys, the most common mutation encountered clinically, reduced susceptibility to cefepime by fourfold. Growth parameter analysis revealed that, conversely, these PB domain mutations generally increase the susceptibility to cefiderocol and piperacillin. The cocrystal structures of PBP3 with β-lactams suggest that the positions of PB domain mutations can affect the mobility of previously proposed key residues, namely, Tyr409, Arg489, Tyr503, Tyr532, Phe533, and the KSGT motif, via intramolecular interactions. These data demonstrated that seven specific variants in ftsI are genetic signals of bacterial adaptation to carbapenems.IMPORTANCEPrevious studies have reported the occurrence of ftsI mutations under various genetic backgrounds in Pseudomonas aeruginosa clinical isolates. However, the nature of ftsI mutations by themselves has not been thoroughly investigated under a common genetic background using recombinant strains. This study presents experimental data on the effect of ftsI point mutations alone on bacterial susceptibility to a wide range of antipseudomonal β-lactams. This study found that seven specific penicillin-binding domain mutations in FtsI/PBP3 reduced the efficacy of carbapenems but increased the efficacies of piperacillin and cefiderocol. This key finding will facilitate the development of therapeutic options for carbapenem-resistant P. aeruginosa-associated infections. Furthermore, this study contributes to the development of a reliable database collating resistance-associated point mutations, which would aid the interpretation of genomic data on P. aeruginosa clinical isolates.